A Matemática na Educação Infantil: um olhar para o Currículo Escolar Municipal de Manaus (AM) - Mafra, Bianca Celestino (BRASIL, 2023)
The present study, with a qualitative and descriptive approach, had the objective of analyzing how mathematical notions are presented in the Municipal School Curriculum of Manaus (CEM) for children in Early Childhood Education (daycare and preschool), through a documentary analysis. The results point to the following mathematical notions present in the document: numbers, quantities and numerical sequence/numerical regularity; counting, recording and numerical notation; solving everyday mathematical problems; geometric shapes; colors; notions/spatial relationships (inside and outside; above and below; above and below; between and on the side); sense of direction; size, weight and thickness; notions about measurement units and magnitudes; and basic concepts of time (now, before, during, after, yesterday, today, tomorrow, slow, fast, fast, slow). However, our analyzes direct us towards a critical-reflexive exercise on the need to be explicit in all fields of Experiences, as mathematical notions in Early Childhood Education cannot be fragmented and disciplined, having as horizon the public policies in the area, the theoretical discussions and especially children as subjects of rights and who produce their own culture.